Measurement properties of performance-based instruments to assess mental function during activity and participation in persons who have survived a stroke: A systematic review protocol. (17th February 2023) - Kristensen, Lola Qvist; van Tulder, Maurits W.; Kristensen, Hanne Kaae; Muren, Marie Almkvist; Mokkink, Lidwine B.; Gregersen Oestergaard, Lisa
Abstract: Background: A frequent consequence of stroke is impaired mental function, which often affects the ability to perform activities and participate in life situation. In occupational therapy practice, performance-based instruments during activity and participation are often used. However, it is important to assess if the instruments used are valid, reliable and responsive. Objective: The objective of this systematic review is to investigate measurement properties of performance-based instruments to assess mental function during activity and participation in persons who have survived stroke. Material and methods: Systematic database searches of PubMed, EMBASE, CINAHL, PsycINFO, and OTseeker will be conducted. COSMIN Risk of Bias checklist will be used to evaluate methodological quality of the included articles. Measurement properties of the included studies will be rated against criteria for good measurement properties. The overall evidence of each measurement property per instrument is graded using a modified GRADE approach. Results: Results will be presented in text and tables. Conclusions: Conclusion will be drawn up-on the overall evidence to give recommendations on the most suitable instrument. Significance: It is expected that findings of the review will provide evidence to guide professionals in the selection of a performance-based instruments to measure mental function in practice and research. Trial registration number: PROSPERO CRD42018086744